Conceptualizing development in information and communication technology for development (ICT4D). Issue 1 (2nd January 2018) - Zheng, Yingqin; Hatakka, Mathias; Sahay, Sundeep; Andersson, Annika
ABSTRACT: ICT4D research is faced with the challenge of rapidly changing technologies and increasingly complex social dynamics and development processes. We argue that ICT4D research requires a more acute sense of where our research is situated within a broader picture of development, e.g. with a better understanding of development processes, their ideological nature, the power structures and driving forces, and the mechanisms through which ICTs may be embedded in and shape these processes. Such a reflexivity is crucial not least in justifying our claims of contribution, but also in understanding the implications and potential impact of our research and practice. This editorial seeks to explore key conceptual components in ICT4D and their relationships, including dimensions of development, perspectives of development, conceptions of artefacts, and theory of change. A tentative conceptual schema is presented that connects these conceptual components.